INTEGRATING SPECTRAL INDICES TO ESTIMATE BIOMASS AND CARBON IN Eucalyptus grandis FORESTS: A CASE STUDY USING NDVI AND CO2FLUX - Guerreiro, Sidnei Fonseca [UNESP]; Kaspary, Rosane Maria [UNESP]; de SOUZA, Flavia Luise Pereira [UNESP]; Martins, Martha Santana; de Campos, Valquíria [UNESP]; Sartori, Anderson Antonio da Conceição [UNESP] (UNESP - Universidade Estadual Paulista, 2024)
Planted forests offer alternatives for reducing greenhouse gases by accumulating biomass in their structure in the carbon cycle and providing the environmental service of carbon sequestration. This reduction needs to be estimated using technologies that can measure the efficiency of these forests and the carbon stock they contain. The purpose of this study was to estimate the values of two spectral indices (NDVI and CO2Flux), using biomass data from a planted forest of Eucalyptus grandis. Three Landsat-8 satellite images taken at orbit/point 221/076 with a spatial resolution of 30 meters were used. The sample points were obtained from a forest inventory conducted in December 2016, covering a total area of 2050 ha, which contained 119,498 trees on six farms located between the municipalities of Borebi and Iaras in the state of São Paulo, belonging to the company Lwarcel Celulose. The results showed high NDVI and CO2Flux indices. NDVI values close to 1 indicate dense, healthy vegetation, such as the reforestation area under study, while high CO2Flux values indicate that the vegetation is absorbing more CO2 than it is releasing, which is positive for carbon sequestration. The study demonstrates the feasibility of adopting the indices for complete data analysis, aggregating and integrating the forest inventory model disseminated by the IPCC with remote sensing for a dynamic assessment of the forestry sector.
INTEGRAÇÃO DE ÍNDICES ESPECTRAIS NA ESTIMATIVA DE BIOMASSA E CARBONO EM FLORESTAS DE Eucalyptus grandis: UM ESTUDO DE CASO COM NDVI E CO2FLUX
Keywords: CO2Flux; Eucalyptus; NDVI; Remote Sensing